Guidance for Processing Reduced Oxygen Packaged (ROP) of Raw, Frozen Seafood in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
This recommended guidance is for frozen seafood that is packaged in a manner that reduces the amount of oxygen in the package below the level normally found in air (anaerobic condition). This condition can alter the growth of spoilage bacteria that normally requires atmospheric oxygen levels (aerobic conditions) for growth. Reduced oxygen packaging (ROP) can include vacuum packaging, and modified or controlled atmospheric packaging (MAP or CAP). These packaging methods can provide the benefit of protecting the product during frozen storage while providing attractive, easy to handle packages with odor control, but in certain circumstances it can also present anaerobic conditions that are favorable for growth and toxin production by a potentially lethal pathogen, Clostridium botulinum. This document is FSHN05-04, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.